Resurgence of diphtheria in Yemen due to population movement - Dureab, Fekri; Müller, Olaf; Jahn, Albrecht (Journal of travel medicine, 2018)
Diphtheria is an epidemic prone bacterial disease caused by a non-encapsulated Gram-positive bacillus (Corynebacterium diphtheria). It may lead to death due to
Gesehen am 27.06.2019